2022
DOI: 10.21037/atm-22-513
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of pembrolizumab combined with paclitaxel and cisplatin as neoadjuvant therapy followed by surgery for locally advanced resectable (stage III) esophageal squamous cell carcinoma: a study protocol for a prospective, single-arm, single-center, open-label, phase-II trial (Keystone-001)

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is one of the most refractory malignant tumors. Esophageal cancer (EC) is a malignant tumor with a high incidence worldwide, and over 50% of EC cases occur in China. Under the National Comprehensive Cancer Network (NCCN) guidelines, concurrent chemoradiotherapy is the only standard neoadjuvant treatment for locally advanced ESCC. In the first-line treatment of advanced ESCC, the efficacy of immune checkpoint inhibitors (ICIs) combined with systemic chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Combination therapy with PD-1 inhibitors results in high rates of surgical conversion; however, further research needs to be conducted to determine the benefits (if any) of PD-1 inhibitors or chemotherapy. According to this study and several previously reported small-sample phase-II prospective studies ( 9 , 16 ), the MPR rate was approximately 60–70% and the pCR rate was approximately 40–50%, which means that 40–50% of the patients did not benefit from treatment with PD-1 inhibitors. The selection of immunotherapy-sensitive populations is a difficult problem in clinical settings.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Combination therapy with PD-1 inhibitors results in high rates of surgical conversion; however, further research needs to be conducted to determine the benefits (if any) of PD-1 inhibitors or chemotherapy. According to this study and several previously reported small-sample phase-II prospective studies ( 9 , 16 ), the MPR rate was approximately 60–70% and the pCR rate was approximately 40–50%, which means that 40–50% of the patients did not benefit from treatment with PD-1 inhibitors. The selection of immunotherapy-sensitive populations is a difficult problem in clinical settings.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, given the recent clinical benefits of paclitaxel in head and neck squamous cell carcinoma and ESCC populations, it has been conjectured that paclitaxel sensitizes tumor cells to T cells, disturbs immunosuppressive mechanisms, and has a strong synergistic effect with PD-1/PD-L1 inhibitors. Thus, in 2 prospective, single-arm, phase-II clinical trials, TD-NICE ( 15 ) and KEYSTONE-001 ( 9 ), researchers used PD-1 inhibitors in combination with paclitaxel and platinum in patients with resectable locally advanced ESCC. The results showed that the R0 resection rates were 97.2% and 100%, the MPR rates were 72% and 72.4%, and the pCR rates were 50% and 41.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the footprint of the KEYNOTE-590 trial, numerous clinical trials of immunotherapy-based neoadjuvant treatment for esophageal cancer were registered. 14 , 15 Most of the trials are still ongoing, and only part of their data have been released at academic conferences. However, no systematic review of the outcomes of current neoadjuvant immunotherapy trials for locally advanced ESCC or EAC has been performed.…”
Section: Introductionmentioning
confidence: 99%
“… 58 Phase II Keystone-001 trial (NCT0438917) and Phase III Keystone-002 trial (NCT04807673) are currently ongoing in China which evaluate the efficacy and safety of pembrolizumab plus chemotherapy (cisplatin plus paclitaxel) over CRT in neoadjuvant setting. 59 , 60 The Phase I PALACE-1 trial, which evaluated the safety of pembrolizumab in combination with neoadjuvant CRT (carboplatin plus paclitaxel with RT), showed high pCR rate of 55.6% and manageable safety, 61 and subsequent Phase II PALACE-2 trial (NCT04435197) is underway. 62 However, the pCR rate of same regimen was poor at 23.1% in the Phase II study (NCT02844075) which conducted in Korea.…”
Section: Future Prospects For Ici Therapymentioning
confidence: 99%